(untitled) (Research, Society and Development, 2026)
Phosphorus (P) has low availability in tropical soils due to strong mineral adsorption. This study aimed to evaluate the solubilization of P during the composting of organic waste associated with reactive natural phosphate FosBio®. The experiment was conducted in Machado, MG, for 60 days, under a randomized block design with six treatments composed of bovine manure, coffee straw, and sawdust, with and without the addition of FosBio®. The contents of total P and its fractions soluble in water, neutral ammonium citrate (NAC + water), and 2% citric acid were analyzed. The inclusion of FosBio® significantly increased soluble P, with the Manure + FosBio® treatment standing out, achieving the highest average solubility (1.68 in citric acid). Waste with a high C/N ratio, such as sawdust, limited solubilization due to microbial immobilization, while coffee straw favored the maintenance of available P. It is concluded that the association between bovine manure and FosBio® with residues of lower C/N ratio is a sustainable alternative for the production of organomineral fertilizers and the building of soil fertility.